Association Between the Results of the Timed Up-andGo Test Adjusted for Disease Severity and Sarcopenia in Patients with Chronic Obstructive Pulmonary Disease: a Pilot Study (Clinics, 2019)
OBJECTIVES: Loss of muscle mass and/or physical performance, a condition commonly known as sarcopenia, is prevalent in chronic obstructive pulmonary disease (COPD) and is associated with adverse outcomes. The aim of this study was to investigate the association between functional performance and sarcopenia in COPD patients classified by disease severity according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria. METHODS: The study was a cross-sectional observational and the sample size consisted of 35 COPD patients (69.24±1.54 years, 20 men). Physical performance was assessed with the timed up-and-go (TUG) test. Sarcopenia was assessed according to the European Working Group on Sarcopenia in Older People criteria. RESULTS: The frequency of sarcopenia was 20% and was more prevalent among individuals classified with greater disease severity, GOLD III, n=4 patients (23%) and GOLD IV, n=3 patients (27%), p=0.83. The mean time to complete the TUG test was 11.66±4.78 s. Binary logistic regression revealed an association between the TUG test and sarcopenia adjusted by disease severity (OR=1.55, 95% CI: 1.03-8.23, p=0.04). CONCLUSION: Our findings showed that worse performance in the TUG test leads to a substantial increase in the chance of COPD patients presenting sarcopenia.